Domain-general auditory processing determines success in second language pronunciation learning in adulthood: A longitudinal study. (5th September 2020) - Saito, Kazuya; Sun, Hui; Tierney, Adam
Abstract: In this study, we propose a hypothesis that domain-general auditory processing, a perceptual–cognitive anchor of first language (L1) acquisition, can serve as an important deciding factor for successful postpubertal second language (L2) pronunciation learning. To examine this hypothesis, samples of spontaneous speech were elicited from a total of 30 L1 Chinese L2 English learners at two points (outset and endpoint) during an 8-month study-abroad period in the United Kingdom. The participants were tested on three different components of auditory processing ability (formant, pitch, and duration discrimination) using behavioral instruments. The auditory processing scores were then linked to the segmental, prosodic, and fluency dimensions of their L2 pronunciation proficiency development throughout the project. Overall, most learners' speech became smoother, faster, and more fluent (fewer pauses, faster articulation rate, and more optimal perceived tempo). Certain learners with high-level auditory processing ability (more precise formant discrimination) appeared to further attain more correct pronunciation of individual sounds and words (greater segmental and word stress accuracy), leading to more advanced L2 phonological skills (fluent and accurate). The findings suggest that auditory processing abilities can be a root of language learning throughout the life span and may apply to the initial- to midphase of naturalistic L2 pronunciation learning in adulthood.